Method for reconstructing waste ternary polycrystalline material into ternary single crystal material

Through crushing and two-step sintering, the used ternary polycrystalline material is reconstructed into ternary single crystal material, solving the complex and cost-effective problems of the existing technology, and realizing low-cost and efficient preparation of ternary single crystal material , has excellent electrochemical properties and high productivity.

CN119287489AInactive Publication Date: 2025-01-10HEFEI GUOXUAN HIGH TECH POWER ENERGY CO LTD CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411192371.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art methods of reconstructing waste ternary polycrystalline materials into ternary single crystal materials are complex, with high process costs and are not conducive to industrial production. The traditional direct recycling method requires additional sorting and separation steps to increase the cost.

Method used

Using a simple seed reconstruction method, the waste ternary polycrystalline material is crushed and mixed with nickel oxide, lithium hydroxide and additives, and recrystallized into a layered oxide positive electrode material through a two-step sintering process, nickel oxide is used as a catalyst, and hydrogen Lithium oxide is used as a lithium supplement agent, and the additive reduces the mixed discharge of lithium-nickel, and combines the rotary kiln process to improve production capacity and particle uniformity.

Benefits of technology

It realizes a three-part single crystal material with low production cost and excellent electrochemical performance, reduces the sintering temperature, improves the sintering rate and production capacity, simplifies the process flow, reduces high-temperature energy consumption, and improves the uniform growth of single crystal material. and structural stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287489A_ABST
    Figure CN119287489A_ABST
Patent Text Reader

Abstract

The invention relates to a method for reconstructing a waste ternary polycrystalline material into a ternary single crystal material, which comprises the following steps: S1, crushing the waste ternary polycrystalline material to obtain single crystal particles; s2, mixing the single crystal particles with nickel oxide, lithium hydroxide and an additive, and presintering to obtain a to-be-repaired material; and S3, sintering and crushing the to-be-repaired material to obtain the ternary single crystal material. According to the invention, after the waste ternary polycrystalline material is crushed, the ternary polycrystalline material is recrystallized into a layered oxide positive electrode material through two-step sintering, and nickel oxide is used as a catalyst to play a role in assisting crystal growth; the lithium hydroxide is used as a lithium supplement agent to supplement lithium consumed by single crystal growth, the additive can reduce lithium and nickel mixing caused by high lithium content in the growth process, the preparation process is simple, the cost is low, and the growth uniformity of single crystals can be improved through a method for directly obtaining single crystal particles after crushing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid waste resource utilization, and in particular to a method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials. Background Art

[0002] With the widespread use of lithium-ion batteries (LIBs), the recycling of these devices has attracted widespread attention. Direct recycling of LIBs is the most effective way to manufacture sustainability because it aims to restore specific cathode materials to their performance before cycling without the need for chemical decomposition of secondary particles. However, the recycled cathode material components may be eliminated by the market. At the same time, traditional direct recycling requires additional sorting and separation steps, which undoubtedly increases costs.

[0003] In order to overcome the above problems, the Chinese patent with publication number CN113998742A provides a method for recycling nickel-cobalt-manganese ternary lithium batteries, dissolving waste positive electrode materials by segmented complex precipitation to obtain a ternary positive electrode material precursor, and finally sintering to obtain a ternary positive electrode material. However, the process of this method is relatively complicated, using solvents such as ammonia water, and poor environmental friendliness. The Chinese patent with publication number CN112391671B provides a method for reconstructing ternary single crystal materials from waste ternary polycrystalline materials, by mixing waste ternary polycrystalline with an organic mixed solvent and then ultrasonically centrifuging, adding lithium manganate seeds and then segmented roasting to obtain a ternary single crystal material with good electrochemical properties. However, the process of this method is relatively complicated and is not conducive to industrial production. Summary of the invention

[0004] Based on this, the purpose of the present invention is to provide a method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials. A simple seed reconstruction method is used to reconstruct waste ternary polycrystalline materials into ternary single crystal materials. Not only can ternary single crystal materials be obtained according to actual content requirements, but also combined with the rotary kiln process, production capacity can be greatly improved, costs can be saved, and ternary single crystal materials with good particle uniformity and excellent electrochemical properties can be obtained.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] The method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials provided by the present invention comprises the following steps:

[0007] S1. Crushing the waste ternary polycrystalline materials to obtain single crystal particles;

[0008] S2. The single crystal particles are mixed with nickel oxide, lithium hydroxide and additives, and then pre-sintered to obtain a material to be repaired;

[0009] S3. Sintering and crushing the material to be repaired to obtain a ternary single crystal material.

[0010] The present invention crushes the waste ternary polycrystalline material and then performs two-step sintering to recrystallize the ternary polycrystalline material into a layered oxide positive electrode material. Nickel oxide is a catalyst to assist crystal growth. Lithium hydroxide is a lithium supplement to supplement the lithium consumed by single crystal growth. The additive can reduce lithium-nickel mixing caused by high lithium content during the growth process. The preparation process of the present invention is simple and low in cost. The single crystal particles obtained directly after crushing can improve the growth uniformity of the single crystal.

[0011] As a further improvement of the above solution of the present invention, in step S1, the waste ternary polycrystalline material is crushed by using a crushing device, and the crushing device adopts a ball mill, a jet mill or a jet mill.

[0012] As a further improvement of the above solution of the present invention, in step S1, the molecular formula of the waste ternary polycrystalline material is Li x Ni a Co b Mn c O2, 1.0≤x≤1.05, a+b+c=1, 0.5≤a<1, 0<b<0.2, 0<c<0.3.

[0013] As a further improvement of the above solution of the present invention, in step S2, the ratio of the single crystal particles, nickel oxide, lithium hydroxide and additive is 1:1:1:0.0002.

[0014] As a further improvement of the above scheme of the present invention, in step S2, the pre-sintering temperature is 400-600°C and the pre-sintering time is 3-6h. By pre-sintering at low temperature, some lithium ions are pre-embedded in the lattice to obtain the repaired material with pre-embedded lithium, which reduces the reaction barrier in the subsequent sintering process, can reduce the sintering temperature by more than 50°C, and reduce high-temperature energy consumption.

[0015] As a further improvement of the above solution of the present invention, in step S2, the additive is at least one of Zr, Ti, Al, Mg, Sr, Nb, V, and Mo. The additive provided by the present invention can reduce lithium-nickel mixing and improve the structural stability of the reconstructed ternary single crystal material.

[0016] As a further improvement of the above solution of the present invention, in step S3, the sintering temperature is 750-900° C., and the sintering time is 5-10 hours.

[0017] As a further improvement of the above solution of the present invention, in step S3, before crushing, the following steps are further included: mixing the sintered material with the coating material and sintering again. By coating, direct contact between the ternary positive electrode material and the electrolyte is prevented, side reactions are reduced, and cycle stability is improved.

[0018] As a further improvement of the above solution of the present invention, the re-sintering temperature is 400-600° C. and the re-sintering time is 5-10 hours.

[0019] As a further improvement of the above solution of the present invention, the coating material is at least one of Al, Co, B, Ti, W, Nb, and V.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention crushes the waste ternary polycrystalline material and then performs two-step sintering to recrystallize the ternary polycrystalline material into a layered oxide positive electrode material. Nickel oxide is a catalyst to assist crystal growth. Lithium hydroxide is a lithium supplement to supplement the lithium consumed by single crystal growth. The additive can reduce lithium-nickel mixing caused by high lithium content during the growth process. The preparation process of the present invention is simple and low in cost. The single crystal particles obtained directly after crushing can improve the growth uniformity of the single crystal.

[0022] 2. The present invention obtains the repaired material pre-embedded with lithium by pre-sintering, which can reduce the temperature required for sintering by more than 50°C and reduce high-temperature energy consumption; in addition, the pre-sintered material can also greatly increase the firing rate, increase the filling volume, and increase the production capacity by more than 20%. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM image of waste ternary NCM523 polycrystalline material in an embodiment of the present invention;

[0024] Figure 2 This is a SEM image of the ternary single crystal positive electrode material prepared in Example 2 of the present invention;

[0025] Figure 3 This is a cycle performance diagram of a button cell prepared using the ternary single crystal positive electrode material prepared in Example 2 of the present invention at a rate of 0.2C. DETAILED DESCRIPTION

[0026] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0028] Example 1

[0029] This embodiment proposes a method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials, and the specific steps are as follows:

[0030] S1. 7.8 mmol of waste ternary NCM523 polycrystalline material was ball milled to obtain single crystal particles;

[0031] S2. The single crystal particles obtained in step S1 are uniformly mixed with 5.2mmol NiO, 5.2mmol LiOH and 2000ppm Zr, and then pre-sintered at a low temperature of 400°C in an air atmosphere in a rotary kiln to obtain a material to be repaired;

[0032] S3. The material to be repaired is sintered in an air atmosphere at 850°C for 8 hours in a roller kiln with a loading amount of 8 kg / bowl, and then crushed by air flow mill to obtain a ternary single crystal NCM622 material.

[0033] Example 2

[0034] This embodiment proposes a method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials, and the specific steps are as follows:

[0035] S1. 7.8 mmol of waste ternary NCM523 polycrystalline material was ball milled to obtain single crystal particles;

[0036] S2. The single crystal particles obtained in step S1 are uniformly mixed with 5.2mmol NiO, 5.2mmol LiOH and 2000ppm Zr, and then pre-sintered at a low temperature of 400°C in an air atmosphere in a rotary kiln to obtain a material to be repaired;

[0037] S3. The material to be repaired is sintered in a roller kiln at 850°C for 8 hours in an air atmosphere with a loading amount of 8 kg / bowl, mixed with a coating agent and sintered again at 450°C for 5 hours, and then jet milled to obtain a ternary single crystal NCM622 material. The coating agent is 2000 ppm Al and 1000 ppm W.

[0038] Example 3

[0039] This embodiment proposes a method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials, and the specific steps are as follows:

[0040] S1. 7.8 mmol of waste ternary NCM523 polycrystalline material was ball milled to obtain single crystal particles;

[0041] S2. The single crystal particles obtained in step S1 are uniformly mixed with 6.9mmol NiO, 5.2mmol LiOH and 2000ppm Zr, and then pre-sintered at a low temperature of 400°C in an air atmosphere in a rotary kiln to obtain a material to be repaired;

[0042] S3. The material to be repaired is sintered in a roller kiln at 780°C for 8 hours in an air atmosphere with a loading amount of 8 kg / bowl, mixed with a coating agent and sintered again at 450°C for 5 hours, and then jet milled to obtain a ternary single crystal NCM811 material. The coating agent is 2000 ppm Al and 1000 ppm W.

[0043] Comparative Example 1

[0044] This comparative example proposes a method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials, and the specific steps are as follows:

[0045] S1. 7.8 mmol of waste ternary NCM523 polycrystalline material was ball milled to obtain single crystal particles;

[0046] S2. The single crystal particles obtained in step S1 are uniformly mixed with 5.2mmol NiO, 5.2mmol lithium carbonate and 2000ppm Zr, and then pre-sintered at a low temperature of 400°C in an air atmosphere in a rotary kiln to obtain a material to be repaired;

[0047] S3. The material to be repaired is sintered in a roller kiln at 850°C for 8 hours in an air atmosphere at a loading rate of 8 kg / bowl, mixed with a coating agent, sintered again at 450°C for 5 hours, and then pulverized by jet mill to obtain a ternary material. The coating agent is 2000 ppm Al and 1000 ppm W.

[0048] Comparative Example 2

[0049] This comparative example proposes a method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials, and the specific steps are as follows:

[0050] S1. After 7.8mmol of waste ternary NCM523 polycrystalline material was uniformly mixed with 5.2mmol NiO, 5.2mmol lithium carbonate and 2000ppm Zr, the mixture was pre-sintered at low temperature at 400°C in an air atmosphere in a rotary kiln to obtain a material to be repaired;

[0051] S2. The material to be repaired is sintered in a roller kiln at 850°C for 8 hours in an air atmosphere with a loading amount of 8 kg / bowl, mixed with a coating agent and sintered again at 450°C for 5 hours, and then pulverized by air jet mill to obtain a ternary material. The coating agent is 2000 ppm Al and 1000 ppm W.

[0052] Test Case

[0053] The waste ternary NCM523 polycrystalline material and the ternary material prepared in Example 2 were characterized respectively. The characterization results are as follows: Figure 1 , Figure 2 As shown, from Figure 2 It can be seen that the NCM622 positive electrode material prepared in Example 2 has good particle uniformity and a high specific surface area.

[0054] The ternary materials prepared in Examples 1-3 and Comparative Examples 1-2 were assembled into button batteries respectively: (1) Preparation of positive electrode sheet: The ternary materials, conductive agent (acetylene black) and binder (PVDF) were weighed in a mass ratio of 80%:10%:10%, and the weighed positive electrode materials and acetylene black were mixed and ground in an agate mortar. After grinding evenly, they were added into N-methylpyrrolidone (NMP) that had been fully reacted with PVDF and continued to grind until the slurry became fluid. The ground slurry is evenly transferred to aluminum foil, and the sample is evenly coated with a coater with a thickness of 150 μm, followed by pre-burning in air at 60°C for 5 hours, and then vacuuming and drying at 90°C for 12 hours to remove water and organic matter from the coated sample, and the electrode sheets are cut out according to size for later use; (2) Button battery assembly: The lithium sheet is used as the negative electrode, the prepared positive electrode sheet is used as the positive electrode, and the electrolyte ratio is EC:DMC=1:1, and they are assembled into button batteries.

[0055] The button cells prepared above were tested for charge and discharge specific capacity: the charge and discharge test was performed using a BTV charge and discharge tester, at 25°C and a test voltage of 3.0-4.3V. The maximum discharge capacity of each button cell at a rate of 0.2C is shown in Table 1. The cycle performance of the button cell prepared from the ternary material prepared in Example 2 at a rate of 0.2C is shown in Table 1. Figure 3 shown.

[0056] Table 1 Button battery test results

[0057]

[0058] from Figure 3 It can be seen that the button cell made from the ternary material prepared in Example 2 has an initial discharge capacity of 178.9 mAh / g, and a capacity retention rate of up to 95.52% after 100 cycles.

[0059] It can be seen from the above test results that the ternary single crystal material in the present invention has a uniform and compact spherical structure, a high discharge specific capacity and excellent cycle stability, and can be used as a commercial lithium-ion battery positive electrode material.

[0060] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0061] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials, characterized in that: It includes the following steps: S1. Crushing the waste ternary polycrystalline materials to obtain single crystal particles; S2. The single crystal particles are mixed with nickel oxide, lithium hydroxide and additives, and then pre-sintered to obtain a material to be repaired; S3. Sintering and crushing the material to be repaired to obtain a ternary single crystal material.

2. The method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials according to claim 1, characterized in that: In step S1, the waste ternary polycrystalline material is crushed by using crushing equipment, and the crushing equipment adopts a ball mill, a jet mill or a jet mill.

3. The method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials according to claim 1, characterized in that: In step S1, the molecular formula of the waste ternary polycrystalline material is Li x Ni a Co b Mn c O2, 1.0≤x≤1.05, a+b+c=1, 0.5≤a<1, 0<b<0.2, 0<c<0.

3.

4. The method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials according to claim 1, characterized in that: In step S2, the ratio of the single crystal particles, nickel oxide, lithium hydroxide and additives is 1:1:1:0.

002.

5. The method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials according to claim 1, characterized in that: In step S2, the pre-sintering temperature is 400-600°C, and the pre-sintering time is 3-6h.

6. The method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials according to claim 1, characterized in that: In step S2, the additive is at least one of Zr, Ti, Al, Mg, Sr, Nb, V, and Mo.

7. The method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials according to claim 1, characterized in that: In step S3, the sintering temperature is 750-900° C. and the sintering time is 5-10 hours.

8. The method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials according to claim 1, characterized in that: In step S3, before crushing, the following steps are also included: mixing the sintered material with the coating material and sintering again.

9. The method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials according to claim 8, characterized in that: The re-sintering temperature is 400-600° C., and the re-sintering time is 5-10 hours.

10. The method for reconstructing waste ternary polycrystalline materials into ternary single crystal materials according to claim 8, characterized in that: The coating material is at least one of Al, Co, B, Ti, W, Nb, and V.

Citation Information

Patent Citations

  • A method for reconstructing ternary single-crystal materials from waste ternary polycrystalline materials

    CN112391671B

  • Recycling method of nickel-cobalt-manganese ternary lithium battery

    CN113998742A

  • High-capacity high-nickel positive electrode material and preparation method thereof

    CN112018341A

  • Ternary single crystal positive electrode material as well as preparation method and application thereof

    CN112301428A

  • Method for preparing {010} crystal face exposed flaky single- crystal ternary electrode material by regenerating a waste lithium ion battery

    CN113265704A